1995
DOI: 10.1111/j.1699-0463.1995.tb01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and surface distribution of CD9 in human eosinophils

Abstract: Expression of CD9 is a feature of both eosinophils and platelets. We have investigated the CD9 expression on resting and activated eosinophils with regard to possibly interacting platelets. Mixed leukocytes were obtained from the platelet‐containing (PC) and platelet‐depleted (PD) peripheral blood of healthy donors. A cell membrane permeabilization technique, the FOG method, enabled us to detect the eosinophils as a separate population and permitted flow cytometric analysis of both surface and intracellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
(3 reference statements)
1
25
1
Order By: Relevance
“…We have demonstrated here that surface expression of CD9 is comparable between human eosinophils and monocyte-derived DCs, further supporting eosinophils as professional APCs. As seen in previous studies, CD9 is abundant on the cell surface of eosinophils to such an extent as to be considered a marker for eosinophils (13). Here, we extend these studies showing, for the first time, the ultrastructural immunolocalization of CD9 in human eosinophils.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have demonstrated here that surface expression of CD9 is comparable between human eosinophils and monocyte-derived DCs, further supporting eosinophils as professional APCs. As seen in previous studies, CD9 is abundant on the cell surface of eosinophils to such an extent as to be considered a marker for eosinophils (13). Here, we extend these studies showing, for the first time, the ultrastructural immunolocalization of CD9 in human eosinophils.…”
Section: Discussionsupporting
confidence: 88%
“…The tetraspanin CD9 is abundantly expressed on the surface of eosinophils and intracellularly, yet the function of CD9 in eosinophils remains unclear (13). Matsumoto and colleagues demonstrated that cross-linking CD9 in isolated human eosinophils with a monoclonal antibody followed by a secondary antibody caused eosinophil "activation," as measured by homotypic aggregation by flow cytometry (14).…”
mentioning
confidence: 99%
“…CD9 is generally found on the cell surface; however, occasionally, it is located intracellularly e.g. in eosinophils and platelets, where it is stored pending transfer to the cell surface upon activation (Fernvik et al 1995, Brisson et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that platelet activation by anti-CD9 antibodies is mediated by the FcgII-receptor [10], which indicate that CD9 can co-operate with other receptors to induce intracellular signalling. In addition, CD9 antigens are known to shed from the cell surface of leukaemic lymphoblasts from patients with acute lymphoblastic leukaemia [11], and an existing intracellular pool of CD9 in eosinophils has been proposed [12]. Taken together, these observations indicate that CD9 plays a role in the initial phase of cell activation.…”
Section: Introductionmentioning
confidence: 92%